A Rare Case of Mixed Ductal Neuroendocrine Tumor of the Pancreas - Viswanathan, Vidya; Kumar, Harsh; Gore, Charusheela; Kurhade, Shrikant; Khan, Rumaanah (Annals of Pathology and Laboratory Medicine, 2021)
Collision tumors are tumors that have at least two types of tumors in the same anatomical site with no area of mixing within the transition zone. In 2010 WHO classification of neuroendocrine tumors consists of an adenocarcinoma component and a neuroendocrine carcinoma component in which each of the components accounts for 30% of the tumor. Such tumors are defined as mixed adenoneuroendocrine carcinomas. Occurrence of exocrine and endocrine tumors of the pancreas is extremely rare. The aim of our study was to describe a case in a 60 years old male who was diagnosed with this rare tumor. Gross, microscopic features and immunohistochemistry were used to diagnose this rare condition. Immunohistochemistry markers such as synaptophysin, chromogranin, EMA and Pan CK were used to come to a definitive diagnosis. Synaptophysin and chromogranin were found to be positive in the neuroendocrine component. EMA and Pan CK were found to be positive in the ductal component. Hence a diagnosis of mixed ductal neuroendocrine tumour (collision tumor) was made.